Criminological Analysis of Ethical Code Violations Committed by Indonesian National Police Officers and Their Implications for Public Trust (A Study at the North Sumatra Regional Police) - Novita Sari, Ridha; Aspan, Henry; Siregar, Mhd. Azhali (International Conference Epicentrum of Economic Global Framework, 2026)
The increasing number of ethical violations committed by members of the Indonesian National Police has become a serious concern in the context of law enforcement and public institutional accountability. This study aims to analyze criminologically the factors causing violations of the police code of ethics within the North Sumatra Regional Police and to examine their implications for public trust in the police institution. The research employed normative juridical methods supported by empirical data through a statute approach, conceptual approach, and case approach. The findings indicate that ethical violations committed by police officers are not merely individual deviations but are also influenced by weak supervision, abuse of authority, organizational culture, pressure within law enforcement practices, and inconsistencies in disciplinary enforcement. In several cases handled by the North Sumatra Regional Police between 2021 and 2025, violations involving extortion, narcotics abuse, abuse of authority, and acts of violence significantly affected public perception of the police institution. The gap between normative legal ideals and practical implementation demonstrates that ethical regulations within the police institution have not been optimally enforced. This condition contributes to declining public confidence and weakens the legitimacy of law enforcement institutions. Therefore, strengthening internal supervision, enhancing transparency in ethical proceedings, improving professionalism, and reformulating ethics-based law enforcement policies are necessary to restore public trust and institutional integrity.